PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PLN (PERSERO) ULTG PALOPO - lestari, tiara; kusdarianto, Indra; wahida, Altri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the influence of work environment and work discipline on employee work performance at PT. PLN (Persero) ULTG Palopo. The research uses an explanatory and descriptive approach, with a population of 50 employees, which is also a sample through census techniques. Data was collected using a Google Form-based questionnaire with research variables including work environment and work discipline as independent variables, as well as work performance as dependent variables. Data analysis was carried out using multiple linear regression with t test (partial) and F test (simultaneous) to test the hypothesis. The results of the study show that partially, the work environment and work discipline have a positive and significant influence on employee work performance. Simultaneously, the two independent variables also have a positive and significant influence on employee work performance.